Coordination and Control - Akram, Muhammad; Ahsan, Marium; Iftikhar, Momina; Rehman, Tansif Ur; Sierra, Francisco Garcia-; Hasibuzzaman, Md. Al; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Fitria, Najmiatul; Altable, Marcos; Sfera, Adonis (Jour Med Resh and Health Sci, 2024)
The basic concepts of coordination and control in biology include the systems that integrate and manage the functions of an organism’s cells, tissues, organs, and systems. Complex communication networks are involved in these processes, such as hormonal regulation, chemical interactions and neuronal signaling. Clarifying physiological processes, organism behavior, and reactions to internal and external stimuli requires an understanding of coordination and control systems. This overview delves into the fundamentals of biological coordination and control, emphasizing molecular signaling pathways, endocrine systems, and neural networks. It also talks about how the deregulation of these pathways affects disease situations and how technological improvements allow them to be investigated and manipulated.